Catecholamine inputs to expiratory laryngeal motoneurons in rats. Issue 3 (8th October 2014) - Zhao, Wen‐Jing; Sun, Qi‐Jian; Guo, Rui‐Chen; Pilowsky, Paul M.
ABSTRACT Many respiration‐related interneurons and motoneurons receive a catecholaminergic input, but the extent and distribution of this input to recurrent laryngeal motoneurons that innervate intrinsic muscles of the larynx are not clear. In the present study, we examined the catecholaminergic input to expiratory laryngeal motoneurons in the caudal nucleus ambiguus by combining intracellular labeling of single identified motoneurons, with immunohistochemistry to reveal tyrosine hydroxylase immunoreactive (catecholaminergic) terminal varicosities. Close appositions were found between the two structures, with 18 ± 5 close appositions per motoneuron (n = 7). Close appositions were more frequently observed on distal rather than proximal dendrites. Axosomatic appositions were not seen. In order to determine the source of this input, microinjections of cholera toxin B subunit (1%, 20 nl) were made into the caudal nucleus ambiguus. Retrogradely labeled neurons, located in the ipsilateral nucleus tractus solitarius and the area postrema, were tyrosine hydroxylase‐positive. Our results not only demonstrate details of the extent and distribution of potential catecholamine inputs to the expiratory laryngeal motoneuron, but further indicate that the inputs, at least in part, originate from the dorsomedial medulla, providing a potential anatomical basis for previously reported catecholaminergic effects on the laryngeal adductor reflex. J. Comp. Neurol. 523:381–390, 2015. © 2014 Wiley Periodicals, Inc.